A numerical model incorporating friction induced temperatures for contact recording applications - Kim, JH; Shin, KH (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2000)
The study deals with the development of a computational procedure for evaluating the temperature rise in layered concentrated contacts of head/disk interface. A transient computational model is utilized, The computational distribution of temperature is obtained with the analytical findings for various composition and contact conditions. This general class of problems can be treated provided that heat generation distribution and layer properties are known. It can also provide tribological evaluation to analyze the thermal pulse that induces thermal signals in the head.
Keywords: LAYERED CONCENTRATED CONTACTS; HEAT PARTITION; INTERFACE